2021
DOI: 10.1021/acsbiomaterials.0c01734
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Electroactivity, Mechanical Properties, and Printability through the Addition of Graphene Oxide to Photo-Cross-linkable Gelatin Methacryloyl Hydrogel

Abstract: The human tissues most sensitive to electrical activity such as neural and muscle tissues are relatively soft, and yet traditional conductive materials used to interface with them are typically stiffer by many orders of magnitude. Overcoming this mismatch, by creating both very soft and electroactive materials, is a major challenge in bioelectronics and biomaterials science. One strategy is to imbue soft materials, such as hydrogels, with electroactive properties by adding small amounts of highly conductive na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 86 publications
2
38
0
Order By: Relevance
“…[ 7 ] It has been established that NSCs exhibit poor survival in very soft (<0.1 kPa) or very hard (>100 kPa) materials and tend to differentiate into neurons in reasonably soft materials (≈0.1–1 kPa) and into glial cells in slightly stiffer materials (≈7–10 kPa). The storage moduli of GM‐based or PPy‐based electroconductive hydrogels applied in the field of myogenic differentiation, skeletal muscle regeneration, and neural tissue engineering ranges from 10 2 –10 4 Pa. [ 35,36 ] In this study, the storage moduli of the GMPE hydrogel was 1056.0 ± 133.1 Pa, which matched neural tissue mechanics (600–3000 Pa) and indicates its suitability for soft nerve tissues engineering. [ 7 ] The conductivity of GMP (1.83 × 10 −3 S cm −1 ) and GMPE (1.49 × 10 −3 S cm −1 ) hydrogels were both superior to that of the GM hydrogel.…”
Section: Discussionmentioning
confidence: 66%
“…[ 7 ] It has been established that NSCs exhibit poor survival in very soft (<0.1 kPa) or very hard (>100 kPa) materials and tend to differentiate into neurons in reasonably soft materials (≈0.1–1 kPa) and into glial cells in slightly stiffer materials (≈7–10 kPa). The storage moduli of GM‐based or PPy‐based electroconductive hydrogels applied in the field of myogenic differentiation, skeletal muscle regeneration, and neural tissue engineering ranges from 10 2 –10 4 Pa. [ 35,36 ] In this study, the storage moduli of the GMPE hydrogel was 1056.0 ± 133.1 Pa, which matched neural tissue mechanics (600–3000 Pa) and indicates its suitability for soft nerve tissues engineering. [ 7 ] The conductivity of GMP (1.83 × 10 −3 S cm −1 ) and GMPE (1.49 × 10 −3 S cm −1 ) hydrogels were both superior to that of the GM hydrogel.…”
Section: Discussionmentioning
confidence: 66%
“…The high absorption coefficient for a 405 nm light through the graphene oxide suggested that the UV light intensity would be significantly attenuated by quenching through dark 3D printed hydrogels. [ 50 ] Therefore, the gold ion crosslinking system allowed the gold ions to diffuse into F127‐LA/AuNP/nSi to crosslink LA ligands and produce gold nanoparticles, which might benefit the electrochemical performance of conductive hydrogels. For example, reduced graphene oxide (rGO) was introduced to fabricate conductive ink.…”
Section: Resultsmentioning
confidence: 99%
“…Some results have shown that graphene oxide (GO) enhanced the mechanical properties and improved the printability and shape integrity of 3D printed structures compared with GelMA alone. 11-13 The enhanced mechanical properties of GO are supposed to be due to the covalent interaction between GO and methacrylate groups on the GelMA chain. 12…”
Section: Introductionmentioning
confidence: 99%